2015
DOI: 10.1093/aobpla/plw014
|View full text |Cite
|
Sign up to set email alerts
|

Trait responses of invasive aquatic macrophyte congeners: colonizing diploid outperforms polyploid

Abstract: Polyploidy (multiple copies of whole genomes) is over-represented in invasive plants and thought to promote their success in novel environments. Understanding functional traits supporting colonization can provide a foundation for development of effective management strategies. We compared how two aquatic invasive congeners differing in ploidy (diploid, decaploid) respond to resource availability (light, nutrients). Counter to our predictions, the diploid congener out-performed the decaploid with nutrient enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…In fact, our results contradict with the recent findings of Grewell et al. (), who found that diploid Ludwigia peploides (floating primrose‐willow) had greater biomass accumulation and growth rates under nutrient‐enriched conditions than the closely related allodecaploid L. hexapetala (water primrose). Because nutrient demands can depend on other physiological and molecular factors, such as RNA quantities and expression patterns, cell sizes, and secondary metabolite concentrations, future studies evaluating cytotype responses to nutrient enrichment would benefit from studying trade‐offs associated with transcriptome size, and cell size versus cell quantity (Sterner and Elser, ; Elser et al., ; Cavalier‐Smith, ; Coate and Doyle, ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In fact, our results contradict with the recent findings of Grewell et al. (), who found that diploid Ludwigia peploides (floating primrose‐willow) had greater biomass accumulation and growth rates under nutrient‐enriched conditions than the closely related allodecaploid L. hexapetala (water primrose). Because nutrient demands can depend on other physiological and molecular factors, such as RNA quantities and expression patterns, cell sizes, and secondary metabolite concentrations, future studies evaluating cytotype responses to nutrient enrichment would benefit from studying trade‐offs associated with transcriptome size, and cell size versus cell quantity (Sterner and Elser, ; Elser et al., ; Cavalier‐Smith, ; Coate and Doyle, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Theoretical models (Tilman, , ; Goldberg, ; Gioria and Osborne, ; Goldberg et al., ) and field experimentations (Schoener, ; Goldberg and Barton, ; Wilson and Tilman, ; Mason et al., ) both suggest that competitive interactions have the largest negative fitness consequences for individuals when there is greater overlap in required limited resources or resource allocation strategies. WGD can result in differences in physiological processes (Schlaepfer et al., ; Grewell et al., ; Van Drunen and Husband, ), environmental tolerances (Maherali et al., ; Jamieson et al., ; Thompson et al., , ), and resource allocation strategies (Bales and Hersch‐Green, ), such that similar cytotypes may share more resource requirements or resource allocation strategies with each other than they do with dissimilar cytotypes. If cytotypes are ecologically differentiated in terms of their nutrient requirements, as is hypothesized here, it is expected that intra‐cytotype competition would be more intense than inter‐cytotype competition—mirroring the stronger effects of intraspecific competition than of interspecific competition frequently observed in natural populations (Adler et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…montevidensis in highly disturbed sites, inferring recruitment from seedbanks. Recent studies also have revealed significant resource allocation to early flowering and seed production (Ruaux et al., 2009; Grewell et al., 2016b; B. J. Grewell, personal observations), suggesting sexual reproduction of L. p . subsp.…”
mentioning
confidence: 98%
“…subsp. montevidensis and polyploid congeners (Rejmánková, 1992; Haury et al., 2014; Smida et al., 2015; Thiébaut and Martinez, 2015; Grewell et al., 2016b). However, the taxon has both asexual and sexual reproductive modes and is self‐compatible.…”
mentioning
confidence: 99%